1998
DOI: 10.1016/s0014-5793(98)00170-7
|View full text |Cite
|
Sign up to set email alerts
|

A new family of orphan G protein‐coupled receptors predominantly expressed in the brain1

Abstract: The cloning of a cDNA encoding a G protein-coupled receptor homologous to the endothelin type B receptor, but unable to bind endothelin, was recently reported and termed ET f R-LP. We report here the isolation of a human cDNA encoding a receptor that is highly related to ET f R-LP and which was therefore termed ET f R-LP-2. Comparison of the two amino acid sequences revealed 68% overall homology and 48% identity. As is the case for ET f R-LP, the new receptor is strongly expressed in the human central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 17 publications
4
89
0
Order By: Relevance
“…1A), consistent with the expression pattern of the Gpr37l1 gene by in situ hybridization (ISH) in whole brain sections of newborn and adult C57BL/6J mice ( Fig. S1 A and B) (17). The receptor protein was found colocalized with the astrocytic glial high-affinity glutamate transporter (Glast), with typical staining of reticular and fibrous structures, in the ML and EGL, respectively ( Fig.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…1A), consistent with the expression pattern of the Gpr37l1 gene by in situ hybridization (ISH) in whole brain sections of newborn and adult C57BL/6J mice ( Fig. S1 A and B) (17). The receptor protein was found colocalized with the astrocytic glial high-affinity glutamate transporter (Glast), with typical staining of reticular and fibrous structures, in the ML and EGL, respectively ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…The reported immunolabeling analysis reveals that the Gpr37l1 protein is specifically and progressively expressed in cell bodies and fibrous processes of cerebellar Bergmann glia from the earliest neonatal phases to the adult stage ( Fig. 1 A and B), whereas it is not expressed in newborn and adult cerebellar granule and Purkinje neuronal cells, as reported (15,17,28). Thus, Gpr37l1 is a specific marker of murine Bergmann astrocytes.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In contrast to the mixed distribution of GPR37, GPR37L1 is highly expressed in astrocytes, with in situ hybridization revealing greatest density of GPR37L1 within the Bergmann glia of the cerebellum (Valdenaire et al, 1998). Microarray studies reported more than 100 times higher expression of GPR37L1 in rat and mice astrocytes compared with neurons (Cahoy et al, 2008; Lovatt et al, 2007; Zhang et al, 2014).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%